2017
DOI: 10.1016/j.ejpb.2017.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Mucin dispersions as a model for the oromucosal mucus layer in in vitro and ex vivo buccal permeability studies of small molecules

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 39 publications
1
14
0
3
Order By: Relevance
“…The epithelium surface of the buccal mucosa is covered by a mucus layer responsible for its lubrication, protection, and hydration. This layer is composed by a viscoelastic network of water (95%) and mucin (5%), a glycoprotein responsible for the viscosity and gel properties of the mucus [26,43]. Thus, many studies have evaluated the interaction between dispersed systems and this glycoprotein with the purpose of predicting the mucoadhesion ability of these systems, which is related to increased interactions with the buccal mucosa and site-specific delivery of drugs and/or bioactive compounds [26,44].…”
Section: Resultsmentioning
confidence: 99%
“…The epithelium surface of the buccal mucosa is covered by a mucus layer responsible for its lubrication, protection, and hydration. This layer is composed by a viscoelastic network of water (95%) and mucin (5%), a glycoprotein responsible for the viscosity and gel properties of the mucus [26,43]. Thus, many studies have evaluated the interaction between dispersed systems and this glycoprotein with the purpose of predicting the mucoadhesion ability of these systems, which is related to increased interactions with the buccal mucosa and site-specific delivery of drugs and/or bioactive compounds [26,44].…”
Section: Resultsmentioning
confidence: 99%
“…62 The cell viability during the permeation studies was indicated by the recorded TEER values, which are in close agreement with previous reports. 40,63 Contrariwise, the viability studies were conducted after the application of pre-dissolved film fractions. The treatment of the TR146 cell line with the fabricated formulations exhibited satisfactory viability of the epithelial cells, even for the maximum dosing profiles.…”
Section: Discussionmentioning
confidence: 99%
“…6c). In addition, an in vitro monolayer model including a mucus layer was developed 47,48 . The TR146 cells was adopted as cell model because they could form an epithelium resembling that of non-keratinized buccal mucosa 49 .…”
Section: Exploration Of the Interaction Mechanisms Between Pva-dopa Fmentioning
confidence: 99%
“…The TR146 cells was adopted as cell model because they could form an epithelium resembling that of non-keratinized buccal mucosa 49 . A mucus layer was deposited onto the TR146 cell monolayers 47,48 . The TR146 cell monolayer model treated with PLGA-PDA NPs were found most obvious in fluorescent intensity ( Fig.…”
Section: Exploration Of the Interaction Mechanisms Between Pva-dopa Fmentioning
confidence: 99%